Horizons of Parental Co-Responsibility in Ibero-America - Molina-Ricaurte, Carlos Jesús (PRAWO i WIĘŹ, 2025)
This study examines the implementation of paternity and parental leave policies in Ibero-America, highlighting the similarities and differences among countries in the region. An exploratory review was conducted in Scopus. The results were filtered by time. Then, matches were found based on abstracts and keywords. Official repositories were subsequently consulted to reach a valid result. Finally, the search was expanded to Google Scholar, which provided additional information and allowed three relevant cases (Chile, Colombia, and Spain) to be selected. This limited the analysis to the Ibero-American sphere. The results reveal significant variations in the duration of leaves and the extent to which they are used, suggesting which countries are more likely to foster greater paternal involvement and reduced gender inequality in the workplace. It discusses how differences in legislation and policies impact fathers’ involvement in childcare and its relation to workplace gender equality. The study highlights the need to strengthen family protection frameworks and parental co-responsibility models in Ibero-America to support a more equitable distribution of childcare responsibilities within families and promote gender equality in the workplace and society. In short, the study provides a critical analysis of parental models across Ibero-America, aiming to inform changes in family dynamics and labor practices throughout the region.